On Semigroup Ideals and Generalized Two Sided Reverse α -3- Derivation in Prime Near-Ring - Ikram Saed (Al-Qadisiyah Journal of Pure Science, 2020)
Let  N be a near –ring  and  is a mapping on N .In this paper, we will introduce the notions of two sided reverse -3-derivation and generalized two sided reverse -3-derivation of N . Then we will study commutativity of N under some conditions determined on semigroup ideals of N .